Strategi Pelayanan Biro Haji dan Umrah dalam Meningkatkan Jumlah Konsumen di Shafira Tour dan Travel Cabang Jember - Ubaidillah, Muhammad Ifan (Maddah: Journal of Advanced Da'wah Management Research, 2023)
Service strategy entails a series of intangible activities occurring through interactions between customers, employees, or other elements provided by a company's service provider, aiming to address customer problems or needs. This study aims to comprehend the service strategy of Shafira Tour & Travel Branch in Jember to increase customer numbers and the challenges it faces. A descriptive qualitative approach was employed, utilizing data collection techniques such as interviews, observations, and documentation. Findings reveal the utilization of the "welcoming attitude" strategy, extending beyond verbal greetings to involve actions aligned with staff directives. The strategy process comprises formulation, implementation, and evaluation stages. The main challenges faced by Shafira Tour & Travel Branch in Jember include competitor rivalry and digital technology advancement, presenting both opportunities and threats. The opportunity lies in leveraging technology to ease marketing efforts, while the threat manifests in price competition with similar competitors in the pilgrimage and umrah travel industry.